2011
DOI: 10.1111/j.1365-2656.2011.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural trade‐offs in response to external stimuli: time allocation of an Arctic ungulate during varying intensities of harassment by parasitic flies

Abstract: Summary1. Macroparasites may be a major factor shaping animal behaviour. Tundra ecosystems inhabited by caribou and reindeer (Rangifer tarandus) are known for large concentrations of ectoparasites including mosquitoes (Culicidae) and black flies (Simuliidae), as well as endoparasitic oestrid flies (Oestridae). 2. Increased intensity and duration of insect harassment because of climatic warming is hypothesized as a potential factor in recent declines of Rangifer across the circumpolar north. Although there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 50 publications
6
87
0
Order By: Relevance
“…This difference may be attributable, in part, to vegetation; coastal habitats typically contain a higher proportion of emerging herbaceous plants compared to areas south of the tree line (Riley, 2011). Furthermore, predation risk and insect harassment can also decrease feeding efficiency in ungulates (Hunter and Skinner, 1998;Barten et al, 2001;Laundré et al, 2001;Hebblewhite et al, 2008), including caribou (Hagemoen and Reimers, 2002;Bergerud et al, 2008;Witter et al, 2012). We surmise that decreased intraspecific competition, relief from biting insects, and lower wolf density on the coast, as reported for other coastal caribou summering areas (Garner and Reynolds, 1986;Heard et al, 1996), may have collectively enhanced the nutritional status of female caribou near the SHB coast.…”
Section: Discussionmentioning
confidence: 84%
“…This difference may be attributable, in part, to vegetation; coastal habitats typically contain a higher proportion of emerging herbaceous plants compared to areas south of the tree line (Riley, 2011). Furthermore, predation risk and insect harassment can also decrease feeding efficiency in ungulates (Hunter and Skinner, 1998;Barten et al, 2001;Laundré et al, 2001;Hebblewhite et al, 2008), including caribou (Hagemoen and Reimers, 2002;Bergerud et al, 2008;Witter et al, 2012). We surmise that decreased intraspecific competition, relief from biting insects, and lower wolf density on the coast, as reported for other coastal caribou summering areas (Garner and Reynolds, 1986;Heard et al, 1996), may have collectively enhanced the nutritional status of female caribou near the SHB coast.…”
Section: Discussionmentioning
confidence: 84%
“…However, when Colman et al (2003) tested this idea, they found that reindeer did not increase grazing time in the evening to compensate for reduced grazing on days when insect harassment was greater. Similarly, Witter et al (2012b) found no compensatory grazing by caribou after days when foraging opportunities were lost to insect harassment.…”
Section: Parasites and Diseasementioning
confidence: 99%
“…There are, of course, the direct effects of the parasitic burden that results from successful parasite attacks, with increasing parasite load in an individual associated with decreasing body condition and reproduction (Thomas and Kiliaan 1990;Albon et al 2002;Hughes et al 2009;Ballesteros et al 2012;Cuyler et al 2012;Pachkowski et al 2013). Second, the behavioural response of Rangifer to insect harassment is detrimental to individuals through a reduction in time spent foraging and increased energy expenditure (Downes et al 1986;Ion and Kershaw 1989;Mörschel and Klein 1997;Hagemoen and Reimers 2002;Skarin et al 2010;Witter et al 2012b). These behavioural responses can result in reduced body condition going into the winter (Helle and Tarvainen 1984;Helle and Kojola 1994;Weladji et al 2003), with negative implications for survival and fecundity (Thomas and Kiliaan 1998a).…”
Section: Parasites and Diseasementioning
confidence: 99%
“…In 2012, when the ponds melted earlier, mosquito emergence closely coincided with caribou calving. Insect harassment drives caribou movement [13,39,40], often to insect-free areas such as snow patches and wind-exposed sites at high elevations that offer less food [13,41,42]. Reduced food intake, caused by phenological mismatch with plants or increased time spent avoiding insect harassment, can decrease calf production and increase calf mortality [27].…”
Section: (C) Ecosystem Consequencesmentioning
confidence: 99%